Exploring physical sensor integration in the design of cost-effective and wearable instrumented ankle foot orthosis: A systematic review - Fika Trifani; Abdul Halim (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The mechanical properties of Ankle-Foot Orthoses (AFOs) play a vital role in enhancing mobility and improving the quality of life in individuals recovering from stroke. Parameters such as stiffness, alignment, and kinetic-kinematic characteristics are critical aspects that require optimization in AFO design and evaluation. Purpose: To investigate the advancement of physical sensor technologies applied in AFO systems. It focuses on enabling practitioners and researchers to obtain objective, real-time data on fitting outcomes, while addressing the limitations associated with traditional, bulky, or high-cost instrumentation. Method:  A literature-based review was conducted to analyze the implementation of various physical sensors integrated into AFOs. Sensor selection was examined in relation to targeted biomechanical outcomes, with attention given to each sensor's operational strengths and constraints to inform optimal usage. Results: Findings indicate that physical sensors significantly enhance data acquisition related to AFO fitting and performance by offering accurate, efficient, and user-friendly measurement capabilities. The diversity of available sensors allows for customization based on specific research or clinical objectives, although careful consideration must be given to each sensor's limitations. Conclusion: The integration of physical sensors into AFO systems represents a promising direction in orthotic development, facilitating evidence-based assessments through wearable and cost-effective technologies. Strategic sensor selection is essential to maximizing the accuracy and utility of AFO outcome measurements in both clinical and research settings.